LA CONTRAVENCION DE HURTO EN LA APLICACIÓN DE PENAS NO PRIVATIVAS DE LIBERTAD PARA PERMITIR LA REHABILITACIÓN DEL INFRACTOR Y REPARACIÓN A LA VÍCTIMA - Ortiz Huaca, Ronny Nicolás (2019)
The present thesis entitled: "THE CONTRAVENTION OF HURT IN THE APPLICATION OF NON-PRIVATIVE PENALTIES OF FREEDOM TO ALLOW THE REHABILITATION OF THE INFRACTOR AND INTEGRAL REPAIR TO THE VICTIM." Is the result of the investigation of a problematic investigation where the penalty is not proportional to the damage committed when the offender is not a repeat offender because it affects the rehabilitation process carried out in the prison. The State, in addition to its criminal policies, also aims to punish society as a useful person, thus it is essential to indicate that in the Organic Integral Criminal Code where it prescribes us in article 209.- the theft contravention that establishes the following: In case the pain does not exceed fifty percent of a unified basic salary of the worker in general, the person will be punished with imprisonment of fifteen days. For the determination of the infraction the value of the thing at the moment of the seizure is considered. But nevertheless, to comply with his criminal sanction within prisons would cause intimidation and quarrels among the other PPL, as well as economic expenses to the State related to food, stay, basic services, and in turn overcrowding, due to the fact that this type of criminal offense can be committed by a majority of people, with a view to re-committing a crime once again, but not as a contravention but as a crime. 5 For all these reasons, I consider the origin of an alternative figure important to punish for their guilt outside the prisons, so as to guarantee the rehabilitation of the offender and the victim in a moral way, knowing that he is doing community work and said work is in compliance To the laws. All these contributions have allowed me to corroborate the existence of my problem, to give way to the application of non-custodial punishment in the violation of theft to the non-repeat offender Therefore, it is required that the State analyze a reform to the Comprehensive Organic Criminal Code, to allow non-custodial penalties to offenders who are not a repeat offender as an object of study and thus prevent this toxic environment from living in prisons.